Pengaruh Jenis Pelarut dan Perbandingan Bahan dengan Pelarut terhadap Ekstrak Warna Kulit Pisang Kepok (Musa paradisiaca F.). - Widiantara, I Gede Esti; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
The aims of this study were to determine the effect of solvent type and their ratio between material and solvent on the color of banana peel extract.The experiment in this study using factorial randomized block design with two factor. The first factor was the solvent type which consists of three levels: n-hexsane, acetone, and ethanol. The second factor was the ratio of the solvent that consists of four levels: 1:6, 1:8, 1:10, and 1:12. The experiment were grouped into 2 group and its implementation in order to obtain 24 experimental units. Variables observed are yield, total carotenoid, and the best color intensity. The results of this study indicate that the comparison of ingredients with solvents significantly affected the total carotenoids and the level of redness (a *) while the yield, brightness (L *), and yellowish level (b *) had no effect. The interaction of solvent types significantly affected the total carotenoids and the level of redness (a *) while the interaction of solvent types on yield, brightness (L *), and yellowish level (b *) had no effect. The type of ethanol solvent with a ratio of material to of solvent (1: 6) is the best solvent that produces extracts of banana peels which produce dye extracts with a yield characteristic of 2,40 ± 0,11 % , carotenoids 0,67 ± 0,00 % , L* 2,40 ± 0,11, a* 56,58 ± 6,92, b* 1,66 ± 0,17 . Keywords: Kepok banana peel, solvent type, ratio between material and solvent, extraction, natural coloring